Kajian Pola Penggunaan Antibiotik Profilaksis Hubungannya Dengan Angka Kejadian Infeksi Daerah Operasi (IDO) Pada Pasien Bedah Digestif Di Rumah Sakit Swasta - Kiki Amelia; Ros Sumarny; Delina Hasan; Hafidh Komar (Faculty of Mathtmatics and Natural Sciences, 2019)
Abstract: Prophylaxis antibiotics are given to prevent surgical site infection (SSI). This study aimed to examine the pattern of the use of prophylaxis antibiotics on the incidence and SSI risk factors. This study was an observational analytic study with a cross sectional design. SSI observation was directly observed in postoperative wounds, the first in the treatment room at the time of dressing change, the second observation was carried out in the surgical clinic at the time of repeated control. The total sample during the study period was 57. The results of this study showed the incidence of SSI in digestive surgery patients was 17.5% (10 out of 57 samples). The most widely used prophylaxis antibiotics ware the third generation cephalosporin group ceftriaxone (96,5%)